Direct observation of prion protein oligomer formation reveals an aggregation mechanism with multiple conformationally distinct species. Issue 17 (26th March 2019) - Sang, Jason C.; Lee, Ji-Eun; Dear, Alexander J.; De, Suman; Meisl, Georg; Thackray, Alana M.; Bujdoso, Raymond; Knowles, Tuomas P. J.; Klenerman, David
Abstract : The aggregation of the prion protein (PrP) plays a key role in the development of prion diseases. Abstract : The aggregation of the prion protein (PrP) plays a key role in the development of prion diseases. In the past decade, a similar process has been associated with other proteins, such as Aβ, tau, and α-synuclein, which participate in other neurodegenerative diseases. It is increasingly recognized that the small oligomeric species of aggregates can play an important role in the development of prion diseases. However, determining the nature of the oligomers formed during the aggregation process has been experimentally difficult due to the lack of suitable methods capable of the detection and characterization of the low level of oligomers that may form. To address this problem, we have utilized single-aggregate methods to study the early events associated with aggregation of recombinant murine PrP in vitro to approach the bona fide process in vivo . PrP aggregation resulted in the formation of thioflavin T (ThT)-inactive and ThT-active species of oligomers. The ThT-active oligomers undergo conversion from a Proteinase K (PK)-sensitive to PK-resistant conformer, from which mature fibrils can eventually emerge. Overall, our results show that single-aggregate methods can provide structural and mechanistic insights into PrP aggregation, identify the potential species that mediates cytotoxicity, and reveal that a range of distinct oligomeric species with different properties is formed during prion protein aggregation.